The effect of caffeine, nap opportunity and their combination on biomarkers of muscle damage and antioxidant defence during repeated sprint exercise - Romdhani, M.; Souissi, N.; Dergaa, I.; Moussa-Chamari, I.; Chaabouni, Y.; Mahdouani, K.; Abene, O.; Driss, T.; Chamari, K.; Hammouda, O. (Biology of Sport, 2022)
To investigate the effect of 20 min nap opportunity (N20), 5 mg · kg-1 of caffeine (CAF) and their combination (CAF+N20) on the biochemical response (energetic biomarkers, biomarkers of muscle damage and enzymatic antioxidants) to the running-based anaerobic sprint test. Fourteen highly trained male athletes completed in a double-blind, counterbalanced and randomized order four test sessions: no nap with placebo (PLA), N20, CAF and CAF+N20. Compared to PLA, all treatments enhanced maximum and mean powers. Minimum power was higher [(mean difference) 58.6 (95% confidence interval = 1.31-116) Watts] after CAF and [102 (29.9-175) Watts] after CAF+N20 compared to N20. Also, plasma glucose was higher after CAF [0.81 (0.18-1.45) mmol·l-1] and CAF+N20 [1.03 (0.39-1.64) mmol·l-1] compared to N20. However, plasma lactate was higher [1.64 (0.23-3.03) mmol ·l-1] only after N20 compared to pre-exercise, suggesting a higher anaerobic glycolysis during N20 compared to PLA, CAF and CAF+N20. Caffeine ingestion increased post-exercise creatine kinase with [54.3 (16.7-91.1) IU·l-1] or without napping [58.9 (21.3-96.5) IU·l-1] compared to PLA. However, superoxide dismutase was higher after napping with [339 (123-554) U·gHB-1] or without caffeine [410 (195-625) U·gHB-1] compared to PLA. Probably because of the higher aerobic glycolysis contribution in energy synthesis, caffeine ingestion resulted in better repeated sprint performance during CAF and CAF+N20 sessions compared to N20 and PLA. Caffeine ingestion resulted in higher muscle damage, and the short nap enhanced antioxidant defence with or without caffeine ingestion.